2005
DOI: 10.1016/j.jmb.2005.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Stimulates L1 Retrotransposition by a Post-transcriptional Mechanism

Abstract: Sequence studies of the human genome demonstrate that almost half of the DNA is derived from mobile elements. Most of the current retrotransposition activity arises from L1 and the L1-dependent, non-autonomous elements, such as Alu, contributing to a significant amount of genetic mutation and genomic instability. We present data demonstrating that nickel chloride, but not cobalt chloride, is able to stimulate L1 retrotransposition about 2.5-fold. Our data suggest that the stimulation occurs at a post-transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 64 publications
2
49
0
Order By: Relevance
“…In addition, diet changes, temperature variations, stress etc. could all affect TE transposition (El-Sawy et al, 2005;Hashida et al, 2006;Ebina and Levin, 2007;Cho et al, 2008). Consequently, activation of TEs could result from the relaxation of epigenetic control induced by environmental changes.…”
Section: The Environment Induces Epigenetic Reprogrammingmentioning
confidence: 99%
“…In addition, diet changes, temperature variations, stress etc. could all affect TE transposition (El-Sawy et al, 2005;Hashida et al, 2006;Ebina and Levin, 2007;Cho et al, 2008). Consequently, activation of TEs could result from the relaxation of epigenetic control induced by environmental changes.…”
Section: The Environment Induces Epigenetic Reprogrammingmentioning
confidence: 99%
“…The open reading frames were cloned into the expression vector pBudCE4.1 (InVitrogen), under control of the CMV promoter. The 5′ UTR expression vector was constructed by subcloning L1.3 5′ UTR sequence into pGL3-basic vector (Promega) to drive the expression of the Firefly luciferase gene (El Sawy et al, 2005).…”
Section: Plasmidsmentioning
confidence: 99%
“…28 Both paraquat and VOSO 4 induced DSBs (Figure 6(b)) but only the latter resulted in retrotranspositions (Figure 6(a)), consistent with previous findings showing that DSBs alone were not sufficient to stimulate retrotransposition of LINE-1. 46 Based on these data we concluded that, first, VL30s and Ty1 elements have different retrotransposition properties, as if VL30s were involved in repairing damaged DNA, as Ty1 elements, 38 then one would expect retrotranspositions to be induced following paraquat treatment. However, this was not the case.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, if other LTR-retrotransposons, consisting of ∼4% of interspersed repeats in the mouse genome, 12 were affected by vanadium then the total insertion burden might severely assault the genome integrity and produce accumulative genetic damage contributing to cellular transformation, as previously suggested. 46 We believe that these genome consequences can be prevented with antiviral drugs such as efavirenz, shown to reduce induced retrotranspositions (Figure 4(d)), serving a targeted inhibition of retrotransposition.…”
Section: Discussionmentioning
confidence: 99%